Dual Mechanism of an Intramolecular Charge Transfer (ICT)–FRET‐Based Fluorescent Probe for the Selective Detection of Hydrogen Peroxide. Issue 24 (28th November 2017) - Liang, Xiao; Xu, Xiaoyi; Qiao, Dan; Yin, Zheng; Shang, Luqing
Abstract: A dual‐mechanism intramolecular charge transfer (ICT)–FRET fluorescent probe for the selective detection of H2 O2 in living cells has been designed and synthesized. This probe used a coumarin–naphthalimide hybrid as the FRET platform and a boronate moiety as the recognition group. Upon the addition of H2 O2, the probe exhibited a redshifted (73 nm) fluorescence emission, and the ratio of fluorescence intensities at λ =558 and 485 nm ( F 558 / F 485 ) shifted notably (up to 100‐fold). Moreover, there was a good linearity ( R 2 =0.9911) between the ratio and concentration of H2 O2 in the range of 0 to 60 μm, with a limit of detection of 0.28 μm (signal to noise ratio (S/N)=3). This probe could also detect enzymatically generated H2 O2 . Importantly, it could be used to visualize endogenous H2 O2 produced by stimulation from epidermal growth factor. Abstract : Double detection power : A dual‐mechanism intramolecular charge transfer (ICT)–FRET fluorescent probe for the selective detection of H2 O2 in living cells has been designed and synthesized (see figure). This probe can detect enzymatically generated H2 O2 and be used to visualize endogenous H2 O2 produced by stimulation from epidermal growth factor.